A study on the potential of sugarcane fibers/polyester composite for tribological applications - Eltayeb, N. S. M. (Elsevier Science, 2008)
The tribo-potential of sugarcane fibre reinforcement in the thermoset polymers for enhancing the adhesive wear resistance has not been explored so far. Hence, the present work aims to explore the possibility of using this natural fibre to reinforce polyester and thus opens a new way to implement locally available inexpensive fibres and produce a new candidate tribo-material for bearing applications. Sugarcane fibre/polyester (SCRP) and glass fibre/polyester (GRP) composites (with chopped fibres of 1, 5, 10 mm length randomly distributed and unidirectional mat fibres) were prepared using compression mould and hand-lay-up techniques. Friction coefficients and wear rates of SCRP and GRP composites were determined under dry sliding contact conditions in parallel and anti-parallel orientations and subjected to different operating parameters such as load, speed and test duration.